The Virtues of Joint Production: Ethical Foundations for Collaborative Organizations - Bernacchio, Caleb; Foss, Nicolai J.; Lindenberg, Siegwart (Academy of Management Review, 2024)
Organizations involve joint production where members engage in purposive coordination and cooperation with others. Scholars have often noted the importance of “moral factors” in facilitating such collaboration but previous research has not adequately explained the nature of these moral factors, how they are embodied within joint production, or why organization members willingly adhere to them. We draw upon virtue ethics to address these questions. We argue that joint production represents a distinct, organization-level practice embodying morally salient standards of professional excellence that contribute to the development of members’ virtues through habituation. We then elaborate microfoundations for this account, developing a virtue ethical account of human agency as directed toward human flourishing such that members willingly adhere to organizational norms and values when they coherently embody goods that contribute to human flourishing.